Jump and sprint force velocity profile of young soccer players differ according to playing position - Hassen, D. B.; Zghal, F.; Peyrot, N.; Samozino, P.; Rebai, H.; Rahmani, A. (Journal of Sports Sciences, 2024)
Our study aimed to compare explosive performance and underlying mechanical determinants explored through F-V profiles in jumping and sprinting among young soccer players based on their playing position. Ninety elite soccer players were categorized into the following positions: goalkeepers, central defenders, wide defenders, central midfielders, wide midfielders, and forwards. Two testing sessions were conducted to measure the 30-metre sprint time (T30) using an over-ground sprint test and jump height (Hmax) through the SJ test. Results demonstrated performance variations among positions. In sprinting, forwards showed greater T30 (4.5 ± 0.14 s) compared to other positions, with goalkeepers exhibiting the lowest T30 (4.86 ± 0.18 s). Forwards also displayed higher maximal theoretical velocity (8.8 ± 0.4 m.s-1) and power output (Pmax) (19.4 ± 2.6 W.kg-1) than other positions, while goalkeepers had the lowest Pmax (16.5 ± 2 W.kg-1). In jumping, forwards (33.2 ± 3.9 cm) and wide-midfielders (33.6 ± 3.8 cm) achieved higher Hmax compared to goalkeepers (29.2 ± 5 cm) and central-midfielders (29.2 ± 3.8 cm). Wide-midfielders (28.5 ± 4.8 W.kg-1) and forwards (27.1 ± 4.3 W.kg-1) surpassed goalkeepers (23 ± 2.8 W.kg-1) and central-midfielders (25.1 ± 3.8 W.kg-1) in Pmax. Our findings reveal substantial position-related disparities in F-V profiles among elite young soccer players, in sprinting and jumping emphasizing the need for position-specific training programmes to optimize player development and on-field performance from an early age.